The Impact of Leadership Style on Employee Job Satisfaction among Employees in Private Healthcare Sector in Riyadh, Saudi Arabia (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to study the impact of leadership styles (Transformational, Transactional and Laissez-faire) on employee job satisfaction among private healthcare sector employees in Riyadh Saudi Arabia. A specially designed questionnaire has been distributed to private healthcare employees 55 responses were received, 54 of them were valid. The findings of this study revealed that Transformational and Transactional leadership have significant positive relationship with employee job satisfaction while Laissez-faire leadership does not have significant effect. The results of this study indicate the importance of effective leadership styles practices in improving employee satisfaction within private healthcare sector.
Keywords: Leadership; Job Satisfaction; Transformational Leadership; Transactional Leadership; Laissez-Faire Leadership